Forestry supply chains - Zvejnieks, Mārtiņš (2015)
Forestry supply chains are a significant part of the Swedish economy. These supply chains are highly susceptible to storms damage. In late 2013 Sweden was hit by multiple storms. This leads to the possibility to research how supply chains react to the shocks that storms cause. The aim of this thesis is to research the costs that storms increase, the actions that are taken within the forestry supply chain, as well as possible benefactors from storms. This thesis bases on previous work on supply chain mapping and cost theories. Three supply chains in Sweden are analyzed – Södra, SCA and Norrskog. By mapping the supply chain and analyzing what costs increase it is possible to get a general view of how supply chains react to shocks. The findings of this thesis are that storms create a tradeoff between loss of quality and loss of efficiency for forestry companies who work with forest owners. In all three cases working with reduced efficiency was preferred over losing the quality of logs. The main cause for the loss of efficiency is increased harvesting expenses from working with storm-felled logs, increased storage costs, and slightly increased costs from hiring external forestry workers and transporters. The main actors in dealing with effects of storms are the forestry companies. The actions that they take to reduce quality loss can be grouped in to three categories – information gathering, capacity building and negotiation. Information is continuously gathered on the storm-felled amount and species. Capacity is built up via hiring additional external forestry workers, transporters and machinery for mills. Negotiations happen with forest owners to put off contracts, with other mills in different regions on selling logs, and with the government on relaxing capacity restricting legislation. Lastly it is concluded that no parties profit from storms. Some parties gain in terms of work stability, the industry gains certainty of being supplied with raw materials and lastly the economy gains from increased business activity.